Log-tangent integrals and the Riemann zeta function - Elaissaoui, Lahoucine; Guennoun, Zine El-Abidine (Mathematical Modelling and Analysis, 2019)
We show that integrals involving the log-tangent function, with respect to any square-integrable function on , can be evaluated by the harmonic series. Consequently, several formulas and algebraic properties of the Riemann zeta function at odd positive integers are discussed. Furthermore, we show among other things, that the log-tangent integral with respect to the Hurwitz zeta function defines a meromorphic function and its values depend on the Dirichlet series , where .